Molt Migration in Relation to Breeding Success in Greater Snow Geese - Reed, Eric T.; Bêty, Joël; Mainguy, Julien; Gauthier, Gilles; Giroux, Jean-François (ARCTIC, 2003)
We describe summer migratory movements by female greater snow geese (Chen caerulescens atlantica) breeding on Bylot Island, Nunavut. We followed 121 radio-collared females between 1997 and 2001 to determine the frequency and timing of their departure from the colony in relation to breeding status, nesting success, and molting chronology. We found that 90% (n = 51) of non-breeders (no nest found) and 97% (n = 29) of failed nesters (nest destroyed or abandoned before hatch) departed the island before molting. The few non-breeders that remained on Bylot Island all summer molted earlier than adults with young, and they appeared to initiate the fall migration before breeding geese. In contrast, only 2% of successful nesters (n = 41) left Bylot Island to molt, and those that did presumably had lost their offspring in the early stages of brood rearing. Thus, the occurrence of a molt migration in greater snow geese appears to be strongly dependent on reproductive status and nesting success. The area used by molt migrants and their habitat requirements during molt remain unknown. We suggest that the paucity of predator-safe areas (such as large water bodies) on Bylot Island may be an important factor that drives the geese to molt elsewhere. Nous décrivons les mouvements migratoires estivaux de la grande oie des neiges (Chen caerulescens atlantica) nichant à l'île Bylot (Nunavut). De 1997 à 2001, 121 femelles munies de radio-émetteurs ont été suivies afin de déterminer la fréquence et le moment de leur départ de la colonie relativement à leur statut reproducteur, leur succès de nidification et la chronologie de la mue. Nous avons trouvé que 90 p. cent (n = 51) des non-reproducteurs (pas de nid trouvé) et 97 p. cent (n = 29) des femelles dont le nid a été détruit ou abandonné avant l'éclosion ont entrepris leur migration avant la mue. Les quelques non-reproducteurs ayant demeuré à l'île Bylot tout l'été ont mué et apparemment entrepris la migration automnale plus tôt que les adultes accompagnés de jeunes. Par contraste, ...